A Geriatric Perspective on Benign Paroxysmal Positional Vertigo. Issue 2 (25th January 2016) - Parham, Kourosh; Kuchel, George A.
Abstract : Benign paroxysmal positional vertigo (BPPV) is the most common cause of vertigo in older adults. Beyond the unpleasant sensation of vertigo, BPPV also negatively affects older adults' gait and balance and increases their risk of falling. As such it has a profound effect on function, independence, and quality of life. Otoconia are the inner ear structures that help detect horizontal and vertical movements. Aging contributes to the fragmentation of otoconia, whose displacement into the semicircular, most commonly posterior canals, can produce rotatory movement sensations with head movement. BPPV is more commonly idiopathic in older adults than in younger individuals, can present atypically, and has a more‐protracted course and higher risk of recurrence. Medications such as meclizine that are commonly prescribed for BPPV can be associated with significant side effects. Dix‐Hallpike and Head Roll tests can generally identify the involved canal. Symptoms resolve as otoconia fragments dissolve into the endolymph, but appropriate canalith repositioning (e.g., Epley maneuver) can expedite recovery and reduce the burden of this disorder. Observations suggesting an association between idiopathic BPPV and vitamin D deficiency and osteoporosis indicate that BPPV may share risk factors with other common geriatric conditions, which highlights the importance of moving beyond purely otological considerations and addressing the needs of older adults with vertigo through a systems‐based multidisciplinary approach.